The effect of public services, motivation and income on employee performance through job satisfaction At the binjai city BPKPAD Office - Andi Antorio Ginting; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to find out and analyze the influence of Public Services, Motivation and Income on Performance mediated by Job Satisfaction at the BPKPAD Office of Binjai City. This research was carried out at the BPKPAD Office of Binjai City. The type of research is quantitative associative. The population in this study is 190 employees with ASN and honorary status in the General Section of the BPKPAD Office in Binjai City. The sampling technique in this study uses the slovin technique which is as many as 129 people. The results of the study show that Public Services have a significant influence on Performance as shown by the T-Statistic value of 10,702 > 1.96 and the P Value of 0.000 < 0.05. The influence of Motivation on performance is shown by a T-Statistic value of 3,209 > 1.96 and a P Value of 0.001 < 0.05 which shows that there is an influence between motivation and employee performance. In the effect of Income on Employee Performance, data on the T-Statistical value was obtained from 3,057 > 1.96 and a P-Value value of 0.001 < 0.05 or there was an effect of Income on Performance. Public Services had a significant effect on Employee Job Satisfaction with a T-Statistic value of 2,393 > 1.96 with a P-Value of 0.031 < 0.05. Motivation has a significant effect on Employee Job Satisfaction. This can be seen from the results of the T-Statistic value of 15,735 > 1.96 with a P-Value of 0.000 < 0.05. On the effect of Income on Job Satisfaction, a T-Statistic value of 4,302 < 1.96 was obtained with a P-Value of 0.000 > 0.05 which means that Income has a significant effect on the Job Satisfaction of Employees of the BPKPAD Office in Binjai City. In the indirect influence of the results, the results show that Job Satisfaction does not have a role as an intervention variable in explaining the relationship between Public Service, Motivation and Income on Performance. This shows that improvements in Public Services, Motivation and Income cannot increase Job Satisfaction, which in the end will not contribute to improving Performance at the BPKPAD Office of Binjai City.